Bacillus velezensis YN2111 reveals the potential role of amine oxidase in Fusarium wilt response in Cavendish bananas - Yu, Hongwei; Zhou, Guangdong; Zhang, Wenlong; Omondi, Bonaventure Aman; Cenci, Alberto; Liu, Kunhua; Liu, Juhua; Fan, Huacai; Li, Shu; Rouard, Mathieu; Zheng, Sijun (Elsevier, 2025)
Fusarium wilt of banana (FWB)—a soil-borne disease caused by Fusarium oxysporum f. sp. cubense (Foc) especially tropical race 4 (TR4)—poses a significant threat to the banana industry. Biological control is a primary strategy for preventing and controlling FWB. In this study, we isolated Bacillus velezensis YN2111 and found that YN2111's metabolic composition exhibits biocontrol properties, including promoting banana growth and inhibiting TR4 in vitro. However, greenhouse pot experiments and laser scanning confocal microscopy revealed that YN2111 can exacerbate FWB by facilitating the entry of TR4 into the plant roots. We speculate that a specific interaction exists among YN2111, Cavendish banana, and TR4. To explore this interaction, we conducted transcriptome sequencing of 64 banana root samples under four different treatments (CK, YN2111, TR4, and YN2111+TR4) at four time points. We subsequently identified a key gene through STEM analysis of DEGs, which encodes a banana amine oxidase (containing copper) involved in the catabolism of polyamines, designated as MuAo (TPM <1). This gene was cloned, and subsequently RT-qPCR results showed that the Ct values of MuAo in samples treated with YN2111 were similar to those in the negative control (using a water template), suggesting that YN2111 treatment effectively inhibited MuAo expression. Combining RT-qPCR results with further inference from literatures, the MuAo may be related to the basal defense of banana, we concluded that YN2111 can block the expression of MuAo in banana roots, suggesting that MuAo could potentially be involved in the process by which YN2111 facilitates the entry of TR4 into the banana roots. Finally, we discussed a novel interaction among YN2111, banana, and TR4, with the outcomes of this research offering a better understanding of Bacillus spp. in biocontrol and microbial-plant interactions, and providing new insights into the exploration of resistance genes against FWB.